Efficacy of L-cet Use in Children with Seasonal Allergic Rhinitis - Yu.G. Antypkin; V.F. Lapshyn; T.R. Umanets; T.V. Kondratenkova (Zaslavsky O.Yu., 2013)
The paper presents the study data on clinical efficacy of antihistamine syrup L-cet in children with seasonal allergic rhinitis. Received data show high therapeutic efficacy and good tolerability of the drug in children.